The effect of a training course on the difference of the number of steps , distance and expended energy for a football game by using a physical electronic performance system EX3 Pedometer - alwan, yaheaa (Journal of Physical Education, 2010)
Research includes five sections: Part I: Definition and importance of researchContains Part One definition of research, it has been addressed through the importance of football as well as the huge development that has occurred on the sport in the world, and the high level of teams participating in tournaments and sports. Systems and devices of modern sports played a big role in the development of training methods and the quality of tests and speed accomplish than the increased attention from trainers in the development of their teams. The research problem defines difference between the results of the tests the first half and second half performance during a football match between the two teams.The research aims to:1. Identify the effect of the training course in the development of some physical abilities and their impact on energy expended.2. Identify the effect of the training course for the difference in the results of the research variables between the first half and second half.3. Identify the effect of the training course for the difference in results between the group (A) and (B). The hypotheses of the research were:1. There are differences of the effect of the training course in the development of some capacity and alternative energy expended in the performance of a football match.Fields of research included the following:1. The human domain: Baghdad Club players in the Premier League. 2. Temporal domain: from 05/04/2010 until the end of the search. 3. Spatial domain: Stadium of Baghdad ClubPart II: Theoretical and similar studies This section contains the theoretical studies, it included the concept of fitness and its components as well as include the concept of energy expended and its types.Part III: Research Methodology and procedures of the FieldResearch used the experimental approach on a sample of Baghdad Club players, consisting of (20) players, this sample was divided into two groups (A) and (B) were subjected to the same training course . The researcher implemented the previous tests which is about a football match and measure the number of steps , distance traveled and energy expended using physical electronic performance system . When we get the results, the researcher write data and results in special forms of the test. The posterior tests has been implemented in the same conditions and specifications that were the pretest. the researcher write data and results in special forms of the test.Part IV: Showing , analyzing and discussion resultsResults were presented and analyzed by teams of community and standard deviations for the difference in the number of steps, distance and expended energy as well as the value of (t) , the significance of the differences and the proportion of development. Part V: Conclusions and recommendations The researcher reached the following conclusions :1. The design of the training course was comprehensive and it is appropriate to the level of capabilities of the players. 2. Training course had a positive impact on the development of the capacity of the players.3. Confirmed the effectiveness of the system of electronic measurement of the number of steps, distance and expended energy. The recommendations were:1. Urged Iraqis trainers to use modern methods in the tests before and after the design of training course . 2. Strengthening the relationship between researchers in education and sports trainers to take advantage of knowledge of new research, especially the modern testing methods.